2020
DOI: 10.3390/ijerph17092996
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Heavy Metals in Electronic Waste Recycling in Thailand

Chalermkhwan Kuntawee,
Kraichat Tantrakarnapa,
Yanin Limpanont
et al.

Abstract: Electronic waste recycling can release heavy metals into the environment and cause adverse health effects. We assessed the association between exposure to heavy metals from electronic waste recycling and the prevalence of asthma in a nested case-control study of 51 subject pairs with and without asthma. House dust, airborne dust, blood, and urine were collected from residents of two neighboring sites in Ubon Ratchathani province, Thailand. Multiple electronic waste-handling activities are conducted in the firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 33 publications
2
3
0
Order By: Relevance
“…In this study, the majority of the exposed group was male (42; 55.3%), with a mean age of 48.00 ± 12.645 years, which was consistent with the study of Thanthisawapop et al [27], who found that the mean age of the exposed group was 48.07 ± 13.19 years. Moreover, most participants completed primary school education (55, 72.4%), consistent with the study by Kuntawee et al [3], which found that most of the EWSW in Thailand were primary school level. Suraraks and Nawwan [49] described that different education levels affect employees' financial compensation.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…In this study, the majority of the exposed group was male (42; 55.3%), with a mean age of 48.00 ± 12.645 years, which was consistent with the study of Thanthisawapop et al [27], who found that the mean age of the exposed group was 48.07 ± 13.19 years. Moreover, most participants completed primary school education (55, 72.4%), consistent with the study by Kuntawee et al [3], which found that most of the EWSW in Thailand were primary school level. Suraraks and Nawwan [49] described that different education levels affect employees' financial compensation.…”
Section: Discussionsupporting
confidence: 90%
“…The concentration of Pb in the blood was consistent with the study by Kuntawee et al [3], which examined the blood lead levels of the exposure group, EWSW in Thailand, and the non-exposed group, farmers. In this study, no statistically significant difference in the blood lead concentrations was identified between the exposed and non-exposed groups.…”
Section: The Comparison Of Concentrations Of Pb CD and Ni In The Bloo...supporting
confidence: 89%
See 2 more Smart Citations
“…E-waste recyclers in a Swedish facility had urinary mercury levels higher than measured in a control group of office workers [38]. In the e-waste recycling site of BanKok and the town of BanKlang, Thailand, urinary mercury was higher in participants involved with e-waste recycling compared to those not handling e-waste [48]. Hair mercury concentrations were higher among compact fluorescent light workers in Gaohong, China, compared with control residents [45].…”
Section: Mercury In Biomarkers Of Populations Exposed To E-wastementioning
confidence: 82%